Assessment of Risk Factors Causing Oral Cancer among Patients Visiting Dental OPD: Oral Cancer among Patients Visiting Dental OPD - Chandio, Benish; Bhutto, Seerat Ul Urooj; Shahzad, Muhammad; Madhuri, Maya; Panhwar, Muhammad Ali; Siddiqui, Amanullah; Kandhro, Rehmatullah (Pakistan Journal of Health Sciences, 2024)
In Pakistan, oral cavity cancer incidence rates are increasing making it the most common cancer, numbered as the second cancer in the list of cancers among males as well as females. Oral cancer is diagnosed frequently and is one of the leading causes of death in Pakistan. Worldwide, oral cancer is 6th most common cancer; in developing countries like Pakistan, India, and Sri Lanka incidence is very high. Objective: To examine the risk factors causing oral cancer among patients visiting the dental Out Patients Department of Liaquat University of Medical and Health Science, Jamshoro/Hyderabad. Methods: A cross-sectional study was done at the Department of Oral and Maxillofacial Surgery Department, Liaquat University of Medical and Health Science, Jamshoro/Hyderabad over a six-month duration. The data were analyzed by using SPSS version 26 employing Pearson’s chi-square test. Results: Male were mostly affected as compared to female (76%). The mean age of the patients was noted as 46.62 years. Buccal mucosa was the most common site affected (45.5%). Smokeless tobacco products and smoking have a significant association with oral cancer (p-value=0.000). Conclusions: It was concluded that smokeless products are used more frequently than smoking and have more risk of increasing the incidence of oral cancer. Among all participants, 115 patients were diagnosed with squamous cell carcinoma.